The Effect of High-Altitude Acclimatisation on Ultra-Short Heart Rate Variability - Boos, Christopher John; Mellor, Adrian; Woods, David Richard; O’Hara, John Paul (Frontiers in Cardiovascular Medicine, 2022)
Introduction High altitude (HA) exposure affects heart rate variability (HRV) and has been inconsistently linked to acute mountain sickness (AMS). The influence of increasing HA exposure on ultra-short HRV and its relationship to gold-standard HRV measures at HA has not been examined. Methods This was a prospective observational study of adults aged >18 years undertaking a HA trek in the Dhaulagiri region of the Himalayas. Cardiac inter-beat-intervals were obtained from a 10-second (s) recording of supra-systolic blood pressure (Uscom BP+ device) and simultaneously from a 300s single lead ECG recording (CheckMyHeart device). HRV was quantified using the RMSSD (root mean square of successive differences of NN intervals) at sea level (SL) in the UK and at 3619m, 4600m and 5140m at HA. Oxygen saturations (SpO2) were measured using finger-based pulse oximetry. The level of agreement between the 10s and 300s RMSSD values were examined using a modified Bland-Altman relative-difference analysis. Results Overall 89 participants aged 32.2±8.8 years (range 18-56) were included of which 70.8% were men. HA exposure (SL vs. 3619m) was associated with an initial increase in both 10s (45.0 [31.0-82.0]) vs. 58.0 [33.0-119.0] ms) and 300s (45.67 [33.24-70.32] vs. 56.48 [36.98-102.0] ms) in RMSSD. Thereafter at 4600m and 5140m both 10s and 300s RMSSD values were significantly lower than SL. From a total of 317 paired HRV measures the 10s and 300s RMSSD measures were moderately correlated (Spearman r=0.66; 95% CI: 0.59 to 0.72: p<0.0001). The median difference (bias) in RMSSD values (300s-10s) was -2.3ms with a lower and upper limit of agreement of -149.5ms and 88.55ms respectively with no differences with altitude. Overall 290/317 (91.4%) of all paired HRV values fell within the 95% CI limits of agreement. Neither HRV method was predictive of AMS. Conclusions Increasing HA affects ultra-short HRV in a similar manner to gold-standard 300s. Ultra-short HRV has a moderate agreement with 300s measurements. HRV did not predict AMS.